Ultrasonic Inspection of a 9% Ni Steel Joint Welded with Ni-based Superalloy 625: Simulation and Experimentation - João da Cruz Payão Filho; Elisa Kimus Dias Passos; Rodrigo Stohler Gonzaga; Ramon Fonseca Ferreira; Daniel Drumond Santos; Diego Russo Juliano (Metals, 2018)
The ultrasonic inspection of thick-walled welded joint with austenitic weld metal has proven to be a challenge due to its anisotropic microstructure that can promote ultrasonic waves attenuation. This work aimed to optimize the phased array ultrasonic inspection of the thick-walled joint of a 9% Ni steel pipe welded with Ni-based superalloy 625. The development was carried out by CIVA numeric simulation to preview the beam behavior during the inspection of GTAW (Gas Tungsten Arc Welding)/SMAW (Shielded Metal Arc Welding) joint with anisotropic weld metal. To validate the simulation results, experimental tests were performed with a phased array transducer using longitudinal waves on a calibration block withdrawn from the joint. The configuration of low frequency (2.25 MHz), 16 active elements and a scanning angle of 48° ensured the inspection of the entire joint and the computational simulation proved to be essential for the success of the inspection.